LEADERSHIP STYLE,ORGANIZATIONAL CULTURE AND INNOVATIVE BEHAVIOR ON PUBLIC HEALTH CENTER PERFORMANCE DURING PANDEMIC COVID-19 - Suprapti, Suprapti; Asbari, Masduki; Cahyono, Yoyok; Mufid, Abdul (Journal of Industrial Engineering & Management Research, 2020)
In the competitive business world today during Pandemic Covid-19, many industries face the flux of rapid change, especially in the Public Health Center. Therefore companies should focus on innovative work behavior (IWB) in order to gain a competitive advantage. This research tested the effect of transformational leadership and organizational climate on work performance through innovative work behavior as mediating by taking the automotive industry in Indonesia. Data collection was carried out by simple random sampling via electronic to a population of Public Health Center employees in Indonesia during Pandemic Covid-19. The returned and valid questionnaire results were 1199 samples. Data processing using SEM method with SmartPLS 3.0 software. Data collection technique is using questionnaire with likert scale. The result was transformational leadership and organizational climate gave a positive effect and significant on work performance, both directly and through mediating innovative work behavior. Innovative work behavior has a positive effect and significant on work performance. This novel research is proposing a model to build work performance among employees of automotive industry through transformational leadership and organizational climate with organizational learning as mediation.